Application of Decision Making from Islamic Perspective by Decision Maker - Mahmudur Rahman; Muhammad Faizul Haque; Naeem Osmani; Idris Ali; Md Atiqur Rahman Sarker (Al Tijarah, 2021)
The primary object of this study is to understand the process of making decision from Islamic perspective and to describe how decision making from Islamic perspective plays important role in the daily life and the planning process. The purpose of this research is also to identify the methods that can be used in making decision and to explain the benefits and advantages of making decision from Islamic viewpoint. This study adopted the qualitative research design and involved 12 participants that includes managers, academicians, social activist and organisation heads who are involved in making decisions as well as the PhD students of social sciences. The data collection procedure was a qualitative in-depth face-to-face and online platform interview. According to the response of the participants, the result of this study shows that decision making from Islamic perspective can avoid from making mistakes and it helps the decision makers to make fair and equitable decisions and to achieve the goals effectively and efficiently. It also helps them to generate better solutions when they face problems during making decision. This study will play a significant role to maintain good relationships with colleagues and everyone in the team or at the workplace. This study suggested that the decision makers should follow the concept of Shūrā (consultation) in the decision-making process and guidelines that has been provided in this research, which reduces the gaps between people of different positions and power.